HUBUNGAN POWER OTOT LENGAN BAHU DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP ACCURACY PUKULAN SMASH BULUTANGKIS PB. RAJAWALI KECAMATAN KANDIS - Efendi, Nurul; Ramadi, Ramadi; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the relationship betweenshoulder muscle power, wrist flexibility and to determine the relationship betweenshoulder muscle power and wrist flexibility to the accuracy results of PB Badmintonsmash. Rajawali, Kandis district. with PB badminton accuracy smash results. RajawaliKandis District. Place of research in the PB field. Rajawali, Kandis district. When thisresearch will be carried out in June 2020. This research is used by using a researchdesign for correlation. Given the total population of less than 100 people, the entirepopulation was sampled (total sampling), namely as many as 20 people. Based on theresults of the study, the analysis results obtained from the Shoulder Arm Muscle Powerdata (X1) to Accuracy Smash (Y) are shown rcount 0.473> r table 0.444. which meansthat there is a significant relationship. From the data on wrist flexibility (X20) to theAccuracy smash (Y), r count 0.749> r table 0.444 means that there is a significantrelationship. From the data on the relationship between shoulder muscle power (X1)and wrist determination (X2) together with the Accuracy smash (Y), it is shown thatrcount is 0.810> r table 0.444. which means that there is a significant relationship.Thus, this research can conclude that there is a significant relationship between thePower of the Shoulder Arm Muscles and Wrist Flexibility on the Accuracy of BadmintonSmash PB.Rajawali, Kandis District.Key Words: Relationship, Power of Shoulder Arm Muscles and Wrist Flexibility, BadmintonSmash Accuracy